Renewable energies and the possibility of mitigating environmental pollution and benefiting from them in Iraq: Renewable energies and the possibility of mitigating environmental pollution and benefiting from them in Iraq - Fares, . Naji (The Gulf Economist, 2023)
The oil sector has maintained its permanence in the global economy through the use of petroleum derivatives such as car fuel, diesel and other derivatives. A time may come when oil is to be implemented, and practical and realistic alternatives must be found through renewable energy such as solar energy, wind energy or water. All these alternatives are available in Iraq or the possibilities of benefiting from nuclear energy. Despite this, the Iraqi economy depends on oil, as oil has a negative impact on nature through environmental pollution caused by oil extraction. This makes the Iraqi economy specialists find an alternative energy source that is equivalent to oil. Therefore, the positive relationship between energy consumption and pollution of the environment is clear, the more there is an increase in oil extraction there is an increase in environmental pollution, and this negatively affects the normal life and increase diseases and other negatives that harm humans and animal plants. The Iraqi cities are witnessing a shortage in the amount of electricity produced on the one hand and provide a speed and direction of wind suitable for the exploitation of electricity generation on the other hand, and must work towards the future planning near to preserve the environment and provide alternative energy for oil in Iraq.